2020
DOI: 10.1007/s11695-019-04276-7
|View full text |Cite
|
Sign up to set email alerts
|

Indications, Operative Techniques, and Outcomes for Revisional Operation Following Mini-Gastric Bypass-One Anastomosis Gastric Bypass: a Systematic Review

Abstract: In addition to being a relatively reversible and less complex operation, mini-gastric bypass-one anastomosis gastric bypass (MGB-OAGB) has demonstrated comparable weight loss and metabolic improvement rates with Roux-en-Y gastric bypass (RYGB). However, surgical strategies for managing its failures and late complications were poorly defined. This article aims to review the indications, operative techniques, and outcomes for revisional surgery following MGB-OAGB. A systematic review was performed using the PubM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(14 citation statements)
references
References 30 publications
(43 reference statements)
0
10
0
3
Order By: Relevance
“…Only three cases have been reported so far in the literature, including one patient with an internal hernia 18 months following SADI-S, 30 and two patients from one series that did not specify the occurrence time frame. 26,31 Stricture at the duodenoileostomy (DI) is another potential complication following SADI-S. Surve et al reported a stricture rate at the DI of 0.3% (5 patients out of 1,328). 5 They also found a statistically significant increase in anastomotic strictures following stapled anastomosis compared with hand-sewn anastomosis at a rate of 2.4 versus 0.1%, respectively.…”
Section: Postoperative Complicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Only three cases have been reported so far in the literature, including one patient with an internal hernia 18 months following SADI-S, 30 and two patients from one series that did not specify the occurrence time frame. 26,31 Stricture at the duodenoileostomy (DI) is another potential complication following SADI-S. Surve et al reported a stricture rate at the DI of 0.3% (5 patients out of 1,328). 5 They also found a statistically significant increase in anastomotic strictures following stapled anastomosis compared with hand-sewn anastomosis at a rate of 2.4 versus 0.1%, respectively.…”
Section: Postoperative Complicationsmentioning
confidence: 99%
“…37 Described as a "mini gastric bypass" by Rutledge in 1997, this technique was conceptualized based on a combination of an antecolic Billroth II loop gastrojejunostomy with Collis gastroplasty, including a 1.5-to 2-m afferent limb length from the ligament of Treitz. 30,31,38 OAGB has been reported as a primary and revision safe and effective procedure, and based on previous reports, OAGB represents 4.5% of the over 685,000 bariatric procedures performed annually across the globe. 39,40 This tendency might be attributed to its efficacy, shorter learning curve, simplification of technical complexity (one anastomosis), lower complications rates, and the alternative for either revisions or conversions if required in the future.…”
Section: One-anastomosis Gastric Bypass/mini Gastric Bypassmentioning
confidence: 99%
“…Dann kann anschließend im zweiten Schritt eine Konversion zum intestinalen Bypass-Verfahren durchgeführt werden. Hiermit können durch eine auf den Oberbauch begrenzte Operation sowie eine kurze Operationszeit die kardiopulmonalen und verfahrenstypischen Komplikationen gesenkt werden [32] Der RYGB wird von einigen Autoren als der "Goldstandard" der Adipositas-bzw. metabolischen Chirurgie bezeichnet.…”
Section: Roux-en-y-magenbypassunclassified
“…Sollte postoperativ ein symptomatisches Refluxleiden vorliegen, kann eine Umwandlung in einen RYGB erfolgen [32,58].…”
Section: Omega-loop-magenbypass (Auch Mini-gastric-bypass Mgb)unclassified
“…Original articles является длина билиопанкреатической петли 200 см от связки Трейтца. Но даже при такой сравнительно небольшой длине отключенного участка тонкой кишки у пациентов, которым была выполнена эта операция, нередко (около 4% всех случаев) наблюдаются явления гипопротеине мии, анемии, дефицита важнейших витаминов и микроэлементов, которые не купируются консервативными методами и требуют повторных восстановительных операций [24,25]. Кроме того, OAGB не лишена одного из значимых недостатков желудочного шунтирования -невозможности выполнения эндоскопического исследования отключенной части желудка и двенадцатиперстной кишки.…”
Section: оригинальные статьиunclassified